Teknologi Near Field Commucation pada Perpustakaan Perguruan Tinggi Berbasis Android - Muhammad Luthfi Hamzah; Ermina Rusilawati (INTECOMS: Journal of Information Technology and Computer Science, 2019)
The library is a place that contains books, articles, papers and reading sources that are arranged as sources of information material. Therefore, with the rapid growth of technology, good management of library management is something that is very important for every college. One of the systems developed in this study is Near Field Communication (NFC) which is a subset of RFID (radio frequency identification). NFC is a technology that can simplify and facilitate transactions, transfer data, and wireless connections between two communication devices that are very close to a few centimeters. This system is designed using an Android device that has NFC technology. By using an NFC-based management system on an Android smartphone it is expected to improve its quality and be able to compete in the current technological era nationally or globally. The purpose of this study is to facilitate students in finding information sources by simply attaching an Android smartphone to the NFC tag attached to the book so as to obtain information about the book. This research method starts from discussing the discussion room, setting goals, discussing literature, analyzing problems, discussing models with UML, Designing systems, managing library information management and testing systems. Related to the completion of work in this study describes the design of library information management applications using Android-based Near Field Communication technology in Higher Education. Keywords:Library, Near Field Commnication, RFID, Android.